2021
DOI: 10.3390/ma14071752
|View full text |Cite
|
Sign up to set email alerts
|

A Research on Durability Degradation of Mineral Admixture Concrete

Abstract: In order to study the degradation laws and mechanisms of admixture concretes with single-added SO42− and composite of Mg2+ and SO42−, respectively, the durability tests were conducted on three types of mineral admixture concretes (concretes with single-added metakaolin (MK), single-added ultra-fine fly ash (UFA), and composite of metakaolin and ultra-fine fly ash (MF), and one reference concrete. In these tests, the 10% Na2SO4 solution and the 10% MgSO4 solution were used as the erosion medium, and the drying-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Consequently, this process effectively mitigates the decline in later compressive strength of the concrete [ 51 ]. Li [ 52 ] and others found that the combination of RBP, slag, and fly ash can effectively improve the 28 d flexural strength of mortar; Chen [ 53 ] and others believed that the mixture of RBP and fly ash could decrease the porosity of the composite cementitious material and increase enhanced erosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this process effectively mitigates the decline in later compressive strength of the concrete [ 51 ]. Li [ 52 ] and others found that the combination of RBP, slag, and fly ash can effectively improve the 28 d flexural strength of mortar; Chen [ 53 ] and others believed that the mixture of RBP and fly ash could decrease the porosity of the composite cementitious material and increase enhanced erosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The expanding forces created by sulfate interacting with the calcium aluminum hydrates to form ettringite caused expansion and cracking. [8][9][10] The P-wave velocity of RuC increases as the immersion period of concrete in NaCl solution increases. RuC's mechanical characteristics improved as rubber particle size increased from 1-3 mm to 3-6 mm but decreased when rubber content increased.…”
Section: Introductionmentioning
confidence: 99%
“…Expansion, cracking, and M‐S‐H (magnesium silicate hydrate) production contributed to the reduction in compressive strength. The expanding forces created by sulfate interacting with the calcium aluminum hydrates to form ettringite caused expansion and cracking 8–10 . The P‐wave velocity of RuC increases as the immersion period of concrete in NaCl solution increases.…”
Section: Introductionmentioning
confidence: 99%
“…The fly ash and slag in traditional mineral admixtures have adverse effects on the mechanical performance of concrete at early stages [25]. However, because of its high pozzolanic activity, metakaolin can promote cement hydration, considerably improving the mechanical performance of concrete at the early stage [26]. Ultra-fine fly ash (UFA) is obtained by processing waste from coal-fired power plants.…”
Section: Introductionmentioning
confidence: 99%